Synthesizing traditions: A framework for integrating classical islamic theology into modern educational paradigms - Much Hasan Darojat; Duna Izfanna; Ahmad Faoisy Aogubado; Anas Fauzi; Miftah Hur Rahman Zh (At Turots: Jurnal Pendidikan Islam, 2025)
In an era of globalization, secularism, and rapid technological change, Islamic theology faces the imperative to remain dynamically engaged with contemporary social, political, and ethical issues. This study systematically maps the current scholarly discourse on integrating traditional Islamic theological principles with modern educational paradigms to meet this challenge. Employing the PRISMA framework, we conducted a systematic literature review of relevant studies published over the past five years from Scopus, Google Scholar, and Web of Science. Our analysis identifies and synthesizes several pivotal trends: a discernible shift in theological discourse from a purely theocentric to a more anthropocentric perspective, the application of theology to modern challenges like economic justice, ethical leadership, and environmental sustainability, and the critical role of contextual hermeneutics. Furthermore, the findings underscore theology's essential engagement with issues of gender equality, interfaith dialogue, and technological ethics. We argue that Islamic theology functions not as a static relic but as a dynamic framework, offering robust ethical guidance for modern Muslim societies. This review provides a synthesized conceptual map of this evolving landscape, offering valuable insights for educators, policymakers, and theologians committed to developing a contextually relevant and inclusive Islamic theological education.